(untitled) (SAARC Journal of Agriculture, 2016)
Calves with optimum health play a crucial role for sustainability of the dairy farms. This study was conducted to evaluate the present status of calf health care and husbandry system on 140 buffalo farms in southern Bangladesh. The data were collected during farm visit and recorded in prepared questionnaire. The results of the present study revealed that significantly lower number of farms (15.0%) had calves with good body condition (p<0.05) during farm visit. Navel cord disinfection to the newly born calves was not practiced in all these farms. Colostrum was fed to calves soon after birth in significantly lower number (4.3%) of farms (p<0.05). Furthermore, 13.6% farmers dewormed their buffalo calves (p<0.05) and calves in 11.4% farms were vaccinated against anthrax and foot and mouth disease (p<0.05). Sick calves were treated by buffalo owner themselves in significantly higher proportion of buffalo farms (59.3%) compared with treated by veterinarian (12.9%) and quack (27.8%) (p<0.05). Overall, the buffalo calf mortality was recorded 14.5% of which higher mortality (74.5%) was observed in first three months of age in comparison to other age groups. Moreover, the number of calves died was affected by herd size in the farms (R2=0.938, p<0.001). The helminthiasis (20.3%) was identified as most prevalent disease in buffalo calves followed by malnutrition (13.2%), indigestion (12.4%) and navel ill (9.3%). It can be concluded that health care and management system of buffalo calves in these dairies are extremely unsatisfactory and buffalo farmers need proper education and training about scientific knowledge of calf rearing practice. SAARC J. Agri., 13(2): 108-120 (2015)